JAK-STAT inhibitors in noninfectious uveitis – A review - Richa Pyare; Nawazish Shaikh; Ahana Sen; Rakshita Kene; Narendra Bagri; Mahesh Janarthanan; Rohan Chawla; Athimalaipet V Ramanan; Parthopratim Dutta Majumder (Indian Journal of Ophthalmology, 2025)
The management of noninfectious uveitis (NIU) has involved the use of corticosteroids and immunomodulators (IMT). However, a certain subset of NIU patients does not respond to conventional IMT therapy, such as methotrexate and azathioprine. In these patients, biological IMT with specific targets is employed. One such example is the use of TNF-α inhibitors, such as adalimumab and infliximab. These biologics target specific inflammatory cytokines, unlike the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway. JAK-STAT inhibitors (JAKinibs) are classified as targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs), which are small-molecule drugs that are chemically synthesized rather than biologically derived. In contrast to biologic DMARDs or bDMARDs, tsDMARDs are smaller molecules that are orally available, nonimmunogenic, and capable of crossing the cell membrane. JAKinibs can simultaneously block multiple cytokine-signalling pathways, such as those driven by IL-6, IL-12, IL-23 and IL-17, as they dampen Th1- and Th17-driven inflammation. This ability to target a broad range of inflammatory cytokines and immune pathways theoretically enables JAKinibs to be viable alternatives for the treatment of NIU resistant to conventional IMT and biologicals. JAK-STAT inhibitors, such as tofacitinib, baricitinib, upadacitinib, peficitinib, delgocitinib, and filgotinib have been FDA-approved for use in autoimmune diseases such as rheumatoid arthritis, psoriatic arthritis, ulcerative colitis, and inflammatory bowel disease. The available literature suggests the potential efficacy of these drugs in controlling uveitic inflammation; however, their use in NIU is still under investigation, with no randomized controlled trials providing Level I evidence.